Identification of c.199-10T>G mutation in SLC25A20 gene related to fatty acid oxidation disorders on a Vietnamese patient - Hoang, Nguyen Huy; Thanh, Duong Chi; Dung, Vu Chi (Vietnam Journal of Biotechnology, 2021)
Fatty acid oxidation disorders (FAODS) consist of rare diseases which affect the energy production of the mitochrondria by disrupting the β-oxidation of fatty acid, resulting in energy deficiency and toxic acumulation in the patient’s body. Typical clinical symtoms of FAODS include rhabdomyolysis, myoglobinuria, cardiomyopathy, hypoketotic hypoglycemia and liver dysfunction on the newborns and could lead to mortality in most of the cases. Mutations occur in different genes in the enzymatic pathway of the mitochrondria may cause diffirent types of FAODS.The objective of this study was to screen and identify genetic mutations associated with fatty acid oxidation disorders in Vietnamese patients through whole exome sequencing analysis. The result revealed a reported homozygous c.199-10T>G mutation in the position of 10 nucleotides before the exon 3 of the SLC25A20 gene. The SLC25A20 gene encodes the carnitine acylcarnitine translocase (CACT), which plays an important role in transporting acylcarnitine and carnitine in the mitochondria. Genetic mutations in this gene often lead to carnitine-acylcarnitine translocase deficiency (CACTD) - a rare form of FAODs. By in silico analysis, the c.199-10T>G mutation was predicted as a splite site mutation that could lead to exon skipping during the creation of mature mRNA. Genetic analysis of the patient’s family showed that both parents had the mutation c.199-10T>G in heterozygous form. This result suggests that every mutant allele in the patient is inherited from parents. Our finding not only improved our understanding of the c.199-10T>G mutation in SLC25A20 gene of our patient but also provides important information for future research, diagnosis and genetic counseling of FAOS in Vietnamese patients.